The efficacy of dopamine versus epinephrine for pediatric or neonatal septic shock: a meta-analysis of randomized controlled studies - Lingling Wen; Liangyin Xu (BMC, 2020)
Abstract Introduction The efficacy of dopamine versus epinephrine for pediatric or neonatal septic shock remains controversial. We conduct a meta-analysis to explore the influence of dopamine versus epinephrine on shock reversal for pediatric or neonatal septic shock. Methods We have searched PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases through July 2019 for randomized controlled trials (RCTs) assessing the efficacy and safety of dopamine versus epinephrine for pediatric or neonatal septic shock. Results Three RCTs are included in the meta-analysis. Overall for pediatric or neonatal septic shock, dopamine and epinephrine reveal comparable shock reversal within 1 h (risk ratios (RR) = 0.61; 95% CI = 0.16 to 2.31; P = 0.47), mortality (RR = 1.16; 95% CI = 0.87 to 1.55; P = 0.30), heart rate (standard mean differences (SMD) = 0.03; 95% CI = -0.28 to 0.34; P = 0.85), systolic blood pressure (SMD = -0.18; 95% CI = -0.69 to 0.33; P = 0.49), mean arterial pressure (SMD = -0.15; 95% CI = -1.64 to 1.34; P = 0.84) and adverse events (RR = 1.00; 95% CI = 0.94 to 1.07; P = 0.91). Conclusions Dopamine and epinephrine show the comparable efficacy for the treatment of pediatric or neonatal septic shock.